Economic evaluation within a factorial-design randomised controlled trial of exercise, manual therapy, or both interventions for osteoarthritis of the hip or knee: study protocol. Issue 1 (17th June 2011) - Pinto, Daniel; Robertson, M Clare; Hansen, Paul; Abbott, J Haxby
Abstract : Introduction: Clinical guidelines for the treatment of hip and knee osteoarthritis recommend non-pharmacological and non-surgical treatments. Exercise treatments are recommended as primary strategies, but specific exercise programme components have not been specified. Early evidence indicates that manual physiotherapy is effective for hip and knee osteoarthritis. The Management of Osteoarthritis (MOA) Trial was designed to evaluate the effectiveness and cost-effectiveness of physiotherapist-led, individualised exercise, manual physiotherapy and a combination of these two interventions in the treatment of adults with hip or knee osteoarthrits. This paper describes the methods that will be used to conduct the economic evaluation of these interventions within the MOA Trial. Methods and analysis: This comprehensive economic evaluation will assess the incremental cost-effectiveness of physiotherapy plus usual care versus usual care alone from a societal perspective. The authors will conduct a cost-consequences analysis using end-points such as Outcomes Measures in Rheumatology Clinical Trials—Osteoarthritis Research Society International responder criteria and quality-adjusted life years. The evaluation will have a time horizon of 1 year (and so discounting will not be necessary). All costs will be reported in 2009 New Zealand dollars. The authors will address uncertainty via bootstrapping to calculate CIs for the mean incremental cost-effectiveness ratios and by performing sensitivity analyses. Ethics and dissemination: Ethical approval was granted by the Lower South Regional Ethics Committee of the New Zealand Ministry of Health (ethics reference: LRS/07/11/044). All participants of the MOA Trial provided written informed consent for the capture of their healthcare costs. We will submit the results of the study for publication irrespective of outcome. Clinical trials registration number: ACTRN12608000130369.